Pressure Induced Changes in Adaptive Immune Function in Belugas (Delphinapterus leucas); Implications for Dive Physiology and Health - Thompson, Laura A.; Romano, Tracy A. (Frontiers in Physiology, 2016)
Increased pressure, associated with diving, can alter cell function through several mechanisms and has been shown to impact immune functions performed by peripheral blood mononuclear cells (PBMC) in humans. While marine mammals possess specific adaptations which protect them from dive related injury, it is unknown how their immune system is adapted to the challenges associated with diving. The purpose of this study was to measure PBMC activation (IL2R expression) and Concanavalin A induced lymphocyte proliferation (BrdU incorporation) in belugas following in vitro pressure exposures during baseline, Out of Water Examination (OWE) and capture/release conditions. Beluga blood samples (n=4) were obtained from animals at the Mystic Aquarium and from free ranging animals in Alaska (n=9). Human blood samples (n=4) (Biological Specialty Corporation) were run for comparison. In vivo catecholamines and cortisol were measured in belugas to characterize the neuroendocrine response. Comparison of cellular responses between controls and pressure exposed cells, between conditions in belugas, between belugas and humans as well as between dive profiles, were run using mixed generalized linear models (α=0.05). Cortisol was significantly higher in wild belugas and OWE samples as compared with baseline for aquarium animals. Both IL2R expression and proliferation displayed significant pressure induced changes, and these responses varied between conditions in belugas. Both belugas and humans displayed increased IL2R expression, while lymphocyte proliferation decreased for aquarium animals and increased for humans and wild belugas. Results suggest beluga PBMC function is altered during diving and changes may represent dive adaptation as the response differs from humans, a non-dive adapted mammal. In addition, characteristics of a dive (i.e., duration, depth) as well as neuroendocrine activity can alter the response of beluga cells, potentially impacting the ability of animals to fight infection or avoid dive related pathologies.